THE EFFECT OF PROBLEM SOLVING METHOD ON THE ANALYSIS ABILITY OF X CLASS STUDENT IN INDONESIAN BIODIVERSITY CONSERVATION EFFORT MATERIAL - Jhon Riswanda; Choirun Niswah; Sulton nawawi; Rina Ardona (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
One of the methods that can be applied to achieve learning goal is the problem solving learning method. Problem solving method is a way or means of presenting lessons by encouraging learners to seek and solve a problem in order to achieve teaching objectives by relating experience and logic. Problem solving methods used to provide learning stimuli to learners to make them think real and analyze, solve problems and then take the conclusions of the problem. This research design using Non-equivalent Control Group Design with Quasi Experimental method (quasi experiment). The sample of this research is 80 students. Based on the results of student ability analysis shows that the implementation of learning using problem solving method is better than conventional learning. The result of the analysis of the average increase of mastery of students’ experimental analysis of the experimental class reached 33,3% while the students' analysis ability in the control class was 19,2%. Keywords: analysis ability, learning method, problem solving